An Analysis of Students’ Ability in Writing Caption Through Instagram - Cut Rosi Maulina (Universitas Syiah Kuala, 2018)
The objective of this research is to investigate the students’ ability in writing caption on Instagram. This research focuses on explaining the result of students’ writing caption in five elements of clarity, conciseness, relevant, context and attractiveness (Grayam, 2010). The data were collected by applying open-ended observation and analyzing the document. The subject of this research were 24 students from class XII-IA 2 whom the researcher followed their Instagram. The data were analyzed by using statistical formula adopted from Rozak (2012). The result of this research showed that the students’ writing caption ability was varied. From five elements of caption, the highest mean score is Attractiveness element with 4.04, followed by Clarity with 3.91, next is Relevant with 3.58, then, Context with 3.37 mean score, the last is Conciseness with 1.5 as the lowest mean score. To conclude, the students’ abilities in writing caption on Instagram are fairly good, even though there were elements need to be improved.